2022
DOI: 10.1002/er.8766
|View full text |Cite
|
Sign up to set email alerts
|

N‐doped oxygen vacancy‐rich NiCo 2 O 4 nanoarrays for supercapacitor and non‐enzymatic glucose sensing

Abstract: Summary Battery‐type transition metal oxides (TMOs) gained great attention as an electrode in a supercapacitor (SC) owing to their high electrochemical activity, however, the performance of SCs influenced by low intrinsic conductivity and lower cycling stability. To address the issues, we propose an effective strategy of nitrogen doping and increasing the oxygen vacancies of hydrothermally synthesized nickel‐cobalt oxide (N‐Ov/NiCo2O4‐350) nanowire arrays. The modified electrode has a variable superficial nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…This showed that appropriate amount of Mo doping can increase the proportion of oxygen vacancies and the number of available active sites, which will improve the electrochemical reaction rate. [46][47] In Mo 3d spectra (Figure 4d), the peak for Mo 6 + 3d 5/2 and Mo 6 + 3d 3/2 were at 232.26 and 235.37 eV, and the peak positioned at 233.08 eV and 236.26 eV should be attributed to Mo 6 + 3d 5/2 and Mo 6 + 3d 3/2 , in consistent with the vibrational peaks from Raman spectra. Based on the above XPS analysis, it can be concluded that the successful doping of Mo element in MoÀ CoO-1 endowed the material more defects and oxygen vacancy, benefiting the nearby Co(II) convert into Co(IV) during the electrochemical process and enhancing the electrochemical catalytic activity of the prepared material.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This showed that appropriate amount of Mo doping can increase the proportion of oxygen vacancies and the number of available active sites, which will improve the electrochemical reaction rate. [46][47] In Mo 3d spectra (Figure 4d), the peak for Mo 6 + 3d 5/2 and Mo 6 + 3d 3/2 were at 232.26 and 235.37 eV, and the peak positioned at 233.08 eV and 236.26 eV should be attributed to Mo 6 + 3d 5/2 and Mo 6 + 3d 3/2 , in consistent with the vibrational peaks from Raman spectra. Based on the above XPS analysis, it can be concluded that the successful doping of Mo element in MoÀ CoO-1 endowed the material more defects and oxygen vacancy, benefiting the nearby Co(II) convert into Co(IV) during the electrochemical process and enhancing the electrochemical catalytic activity of the prepared material.…”
Section: Resultssupporting
confidence: 74%
“…It can be clearly seen that the proportion of oxygen vacancy in Mo−CoO‐1 is 47 %, which is significantly increased compared with 34 % and 40 % of the other two samples. This showed that appropriate amount of Mo doping can increase the proportion of oxygen vacancies and the number of available active sites, which will improve the electrochemical reaction rate [46–47] . In Mo 3d spectra (Figure 4d), the peak for Mo 6+ 3d 5/2 and Mo 6+ 3d 3/2 were at 232.26 and 235.37 eV, and the peak positioned at 233.08 eV and 236.26 eV should be attributed to Mo 6+ 3d 5/2 and Mo 6+ 3d 3/2 , in consistent with the vibrational peaks from Raman spectra.…”
Section: Resultssupporting
confidence: 63%
“…As shown in Figure S16 (Supporting Information), the broad oxidation peak (A 1 ) in the first CV cycle from 1.2 to 1.4 V belongs to the M 2+ /M 3+ (M = Ni and Co) redox couples, and the peak (A 2 ) at ≈1.50 V corre-sponds to the Co 3+ /Co 4+ oxidation process. The whole process is described by the following reactions: [70,71] NiCo…”
Section: Resultsmentioning
confidence: 99%
“…Previous works have revealed that the Co 2+ and Ni 2+ sites were oxidized to CoOOH and NiOOH as the active sites for oxygen electrocatalysis. [45,[70][71][72][73][74][75] On the other hand, the cathodic sweep from 1.6 to 1.1 V also exhibits a broad peak (C 1 ) at ≈1.44 V and a small peak (C 2 ) at ≈1.18 V, which are identified as the reduction of Co 4+ to Co 3+ and M 3+ to M 2+ , respectively. It is clearly shown in Figure S17 (Supporting Information) that the C 2 peak for M 3+ to M 2+ is negligible, and meanwhile, the A 1 peak for M 2+ to M 3+ in the second and followed CV curves are much lower than that in the first CV curves, suggesting that the pre-oxidation of M 2+ to M 3+ in the first anodic sweep is an irreversible reaction, which provides a stable catalytic surface for the oxygen electrocatalysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, spinel are relatively mature nanomaterials developed for biomimetic catalysis of glucose. Seong et al [ 73 ] proposed an effective nitrogen doping strategy to synthesize the oxygen vacancy of Ni-Co oxide (N-Ov/NiCo 2 O 4 -350) nanowire arrays. The modified electrode has obvious nanoporous structure and favorable electronic structure, thus significantly increasing the specific surface area and suitable electron/ion diffusion network.…”
Section: Biomimetic Nanomaterialsmentioning
confidence: 99%